A new species of the genus Perissus Chevrolat, 1863 (Coleoptera: Cerambycidae) from China - Xie, Guang-Lin; Chen, Jia-Ling; Cui, Ya-Qin (Zootaxa, 2025)
In the current study, a new species of the genus Perissus Chevrolat, 1863 (Cerambycidae: Cerambycinae), named Perissus yangmingae sp. nov. (阳明跗虎天牛) from Shanxi, China, is described and illustrated, along with photographs of the living adult.